Quality of service and scheduling performance optimization in LTE networks / Abubakar Auwal Idris - Abubakar Auwal , Idris (2017)
Long Term Evolution (LTE) is a technology introduced by Third Generation Partnership Project (3GPP) specification to transmit high data rate and increases applications requirements with reliable and best connection. LTE is marketed as 4G cellular network technology. It is a packet switch network designed with features such as supporting high data rate in both downlink and uplink channel. It also supports user in higher mobility cell and allows multi-user scheduling of radio resource. Scheduling is a Radio Resource Management mechanism (RRM) used to allocate radio resources to the user's channel bandwidth. Scheduling plays a vital role to provide Quality of Service (QoS) over the LTE networks. However, daily usage of the current scheduling schemes have degrade the overall system performance, which resulted in reducing the QoS for LTE system. This research proposed an optimal downlink scheduling algorithm called Video Real-Time Scheduling Algorithm (VRTSA) to support real-time traffic of video in LTE network. The developed algorithm is simulated in LTE-Sim simulator released 5 in terms of three QoS metrics (1) Packet Loss Ratio (2) Delay (3) Throughput. The developed scheduling algorithm is accomplished in three methodological stages as follows: first, frequency domain was considered for efficient scheduling at Resource Blocks (RBs) to the users based on best Channel Quality Indicator (CQI) report send from mobile station called as User Equipment (UE) to the base station (eNodeB). Second, time domain is also considered for controlling queue and prediction delay of the late coming expired packet. Third, termination processing unit is created for termination late expired packets those did meet the delay requirements. The performance of the developed VRTSA is evaluated and compared with three well-known downlink scheduling algorithms in LTE such as Proportional Fair (PF), Modified Largest Weight Delay First (MLWDF), Exponential Proportional Fair (EXP/PF) as well as recent algorithm called LTTI. The results have shown that the developed VRTSA has outperformed others in terms of QoS metrics with 1. low packet loss ratio 2. low packet delivery delay 3. maximized system throughput. The result demonstrated using LTE-Sim is achieved to satisfied the QoS requirements in terms of packet loss rate, delay and system throughput. This study simulated single cell scenario with interference, and covered the area with radius 1 Km having a speed of 3Km/h and consists the number of users up to 20 also moving in a random direction at pedestrian and vehicular (PED A and VEH B) channels. The future work will consider to simulate multi cell scenario and the system complexity evaluation.